1974
DOI: 10.1111/j.1476-5381.1974.tb09664.x
|View full text |Cite
|
Sign up to set email alerts
|

THE CARDIOVASCULAR EFFECTS OF l‐DOPA IN THE PITHED RAT

Abstract: I L-DOPA (1-2 mg i.v.) in the pithed rat reduced the arterial and increased the venous pressure responses to noradrenaline.2 Infusions of dopamine (4-8 ,ug kg-' min-) and noradrenaline (500 ng kg-min-') also reduced the pressor responses to noradrenaline. The pressor response did not recover after stopping dopamine infusions, but it usually did so after stopping noradrenaline infusions. 3 The effect of L-DOPA on the response to noradrenaline was prevented by the prior injection of the dopa decarboxylase inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1976
1976
1986
1986

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…L-DOPA increased both blood pressure and heart rate in the pithed rat after either intravenous or intraduodenal administration. From the literature, such effects can be suppressed by prior treatment with inhibitors of AADC (Henning & Rubenson, 1970a,b;Eden & Nasmyth, 1974), which implicates dopamine and/or noradrenaline as the agents responsible for the cardiovascular effects. Presumably, these amines either act directly to stimulate cardiovascular adrenoceptors or, in the case of dopamine, in part indirectly by displacing noradrenaline from its stores within peripheral sympathetic nerves (Farmer, 1966;Tsai et al, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…L-DOPA increased both blood pressure and heart rate in the pithed rat after either intravenous or intraduodenal administration. From the literature, such effects can be suppressed by prior treatment with inhibitors of AADC (Henning & Rubenson, 1970a,b;Eden & Nasmyth, 1974), which implicates dopamine and/or noradrenaline as the agents responsible for the cardiovascular effects. Presumably, these amines either act directly to stimulate cardiovascular adrenoceptors or, in the case of dopamine, in part indirectly by displacing noradrenaline from its stores within peripheral sympathetic nerves (Farmer, 1966;Tsai et al, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…That the long exposure to catecholamines of tissues receiving a sympathetic innervation results in a reduced response of those tissues to catecholamines is well established (Blacket, Pickering & Wilson, 1950;Duner & von Euler, 1957;Trendelenburg, 1971;Eden & Nasmyth 1974;Langer & Dubocovich, 1977). The latter authors showed for the first time that presynaptic as well as postsynaptic responses are Table 3 The effect of noradrenaline (NA) and acetylcholine on the tone of the mouse isolated vas deferens before and after perfusing magnesium-free Krebs solution containing noradrenaline (3 x 10-6 M-2 x 10-5 M) through the organ-bath for 30 min; the effects of the addition of cocaine (10-5 M) affected.…”
Section: Discussionmentioning
confidence: 99%